2017
DOI: 10.1007/s00429-017-1411-5
|View full text |Cite
|
Sign up to set email alerts
|

Addressing sufficiency of the CB1 receptor for endocannabinoid-mediated functions through conditional genetic rescue in forebrain GABAergic neurons

Abstract: Genetic inactivation of the cannabinoid CB1 receptor gene in different cell types in the brain has previously revealed necessary functions for distinct synaptic plasticity processes and behaviors. Here, we sought to identify CB1 receptor expression sites that are minimally required to reconstruct normal phenotypes. In a CB1-null background, we re-expressed endogenous CB1 receptors in forebrain GABAergic neurons, thereby assessing the sufficiency of CB1 receptors. Depolarization-induced suppression of inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 86 publications
4
45
0
Order By: Relevance
“…Specificity control experiments of the CB 1 receptor antibodies were carried out in CB 1 ‐KO and STOP‐ CB 1 mice (carrying a loxP‐flanked stop cassette inserted into the sequences of the 5'UTR of the CB 1 receptor). According to recent observations, we detected very low levels of metal particle deposits in STOP‐ CB 1 (Remmers et al, ) and scattered background particles in CB 1 ‐KO.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Specificity control experiments of the CB 1 receptor antibodies were carried out in CB 1 ‐KO and STOP‐ CB 1 mice (carrying a loxP‐flanked stop cassette inserted into the sequences of the 5'UTR of the CB 1 receptor). According to recent observations, we detected very low levels of metal particle deposits in STOP‐ CB 1 (Remmers et al, ) and scattered background particles in CB 1 ‐KO.…”
Section: Discussionsupporting
confidence: 69%
“…The GFAP‐ CB 1 ‐RS mouse expressing CB 1 receptors exclusively in astrocytes described here, together with the Glu‐ CB 1 ‐RS rescue mouse expressing the receptor only in dorsal telencephalic glutamatergic neurons (de Salas‐Quiroga et al, ; Lange et al, ; Ruehle et al, ; Soria‐Gómez et al, ) and the GABA‐ CB 1 ‐RS rescue mouse expressing the CB 1 receptor only in GABAergic neurons (de Salas‐Quiroga et al, ; Lange et al, ) that were recently characterized anatomically (Gutiérrez‐Rodríguez et al, ; Remmers et al, ), suggest that the regulation of the CB 1 receptor expression in astrocytes, glutamatergic neurons and GABAergic neurons may be independent of each others. The present demonstration that the GFAP‐ CB 1 ‐RS in the hippocampus maintains the normal CB 1 receptor expression and distribution in astrocytes make these mutants ideal suited for the study of the astroglial CB 1 receptor function, as shown for Glu‐ CB 1 ‐RS (de Salas‐Quiroga et al, ; Gutiérrez‐Rodríguez et al, ; Lange et al, ; Ruehle et al, ; Soria‐Gómez et al, ) and GABA‐ CB 1 ‐RS mice (de Salas‐Quiroga et al, ; Gutiérrez‐Rodríguez et al, ; Lange et al, ; Remmers et al, ). In fact, these rescue strategies have the advantage of the restoration and visualization of existing CB 1 receptor levels in locations with sparse CB 1 receptors (as the astrocytes and astroglial mitochondria), allowing a more comprehensive functional characterization of the (endo)cannabinoid system based on the precise cellular and subcellular localization of the CB 1 receptor.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Finally, although Cnr1 −/− mice had similar mortality to double‐knockouts, they did not show spontaneous seizure activity, suggesting that early mortality is driven by factors other than seizures. Other groups have reported increased mortality in Cnr1 −/− mice, but the cause remains unclear. Cardiovascular or other neurological problems besides seizures could lead to the observed increase in mortality.…”
Section: Discussionmentioning
confidence: 95%